(untitled) (Bangladesh Veterinarian, 2010)
The relationship between the scrotal circumference and semen volume, sperm concentration and number of sperm per ejaculate of 12 crossbred bulls [4 Local × Friesian, 4 Local × Sahiwal] was studied. Semen of three consecutive collections at seven day intervals was evaluated. The age of bulls at first collection varied between 15 and 20 months. Soon after collection, volume, sperm concentration, number of spermatozoa per ejaculate and initial sperm motility of fresh semen were measured. Scrotal circumference was correlated with semen volume, sperm concentration and number of spermatozoa per ejaculate in both groups. A significant (P<0.04) positive correlation (r = 0.72) was observed between scrotal circumference and volume of semen, and between scrotal circumference and number of sperm production per ejaculate. Significant (P<0.05) variation was observed in different semen parameters between bulls within the same group, but no significant (P>0.05) variation was found between the two groups. It is suggested that crossbred bulls aged 18 months or over, with scrotal circumference more than 30 cm, yielded good quality semen. DOI: 10.3329/bvet.v26i2.4952 Bangl. vet. 2009. Vol. 26, No. 2, 61-67